The moderating role of gender on the relationship between primary school students' reading attitudes and reading comprehension - Wan Norudin, Siti Wan Aminah; Che Hasan, Norlizah; Mohamed Mokhtar, Marzni; Yasin, Maizurah; Ramli, Mohd Shahridwan (Human Resource Management Academic Research Society, 2024)
Reading comprehension is fundamental to academic progress as it underpins learning across all school subjects. While academic achievement has traditionally been linked to students' cognitive abilities, it is also crucial to consider non-cognitive factors, such as the gender of students. Research has shown gender differences may have influence various aspects of education for students. Therefore, this study investigates gender of student as moderator between students' reading efficacy and reading comprehension. It is a quantitative study using a cross-sectional survey approach. A total of fifteen primary schools in Kelantan involving 393 year five pupils included for the study sample. The participants were identified utilizing a multi-level random sampling procedure. The design of the research includes descriptive tests as well as inferential analysis using structural equation modelling. The data obtained were analysed using structural path analysis within Structural Equation Modelling. The structural path analysis revealed that students' reading efficacy significantly influences their reading comprehension. The moderation analysis indicated a partial moderator effect as there is significant regression coefficients for gender of students, demonstrating that students' reading efficacy on reading comprehension depends on the gender. Therefore, it is crucial to carefully consider gender differences of students when planning educational programs. Gaining a deeper understanding of how students' reading efficacy impacts reading comprehension in relation to their gender can help develop more effective and comprehensive educational strategies for students.